Role of endoscopy in the diagnosis of autoimmune pancreatitis and immunoglobulin G4‐related sclerosing cholangitis. Issue 5 (8th April 2014) - Kamisawa, Terumi; Ohara, Hirotaka; Kim, Myung Hwan; Kanno, Atsushi; Okazaki, Kazuichi; Fujita, Naotaka
<x xml:space="preserve">Abstract</x> Autoimmune pancreatitis (AIP) must be differentiated from pancreatic carcinoma, and immunoglobulin (Ig)G4‐related sclerosing cholangitis (SC) from cholangiocarcinoma and primary sclerosing cholangitis (PSC). Pancreatographic findings such as a long narrowing of the main pancreatic duct, lack of upstream dilatation, skipped narrowed lesions, and side branches arising from the narrowed portion suggest AIP rather than pancreatic carcinoma. Cholangiographic findings for PSC, including band‐like stricture, beaded or pruned‐tree appearance, or diverticulum‐like outpouching are rarely observed in IgG4‐SC patients, whereas dilatation after a long stricture of the bile duct is common in IgG4‐SC. Transpapillary biopsy for bile duct stricture is useful to rule out cholangiocarcinoma and to support the diagnosis of IgG4‐SC with IgG4‐immunostaining. IgG4‐immunostaining of biopsy specimens from the major papilla advances a diagnosis of AIP. Contrast‐enhanced endoscopic ultrasonography (EUS) and EUS elastography have the potential to predict the histological nature of the lesions. Intraductal ultrasonographic finding of wall thickening in the non‐stenotic bile duct on cholangiography is useful for distinguishing IgG4‐SC from cholangiocarcinoma. Endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) is widely used to exclude pancreatic carcinoma. To obtain adequate tissue samples for the histological diagnosis of AIP, EUS‐Tru‐cut biopsy or EUS‐FNA using a 19‐gauge needle is recommended, but EUS‐FNA with a 22‐gauge needle can also provide sufficient histological samples with careful sample processing after collection and rapid motion of the FNA needles within the pancreas. Validation of endoscopic imaging criteria and new techniques or devices to increase the diagnostic yield of endoscopic tissue sampling should be developed.